Availability and readiness of health facilities providing services for other infectious diseases to treat neglected tropical diseases in Ethiopia: implications for service integration in high burden areas - Getahun Asmamaw; Tefera Minwagaw; Mastewal Samuel; Wondim Ayenew (BMC, 2024)
Abstract Background The burden of neglected tropical diseases (NTDs), HIV/AIDS, tuberculosis, and malaria pose significant public health challenges in Ethiopia. This study aimed to the explore service availability and readiness for NTD care among Ethiopian health facilities treating tuberculosis (TB), HIV/AIDS, and/or malaria. Methods This study utilized secondary data from the Ethiopian Service Provision Assessment 2021-22 survey. The availability of services was calculated as the percentage of HIV/AIDS, tuberculosis, or malaria facilities providing NTD services. Facilities were considered highly prepared to manage any type of NTD if they scored at least half (> 50%) of the tracer items listed in each of the three domains (staff training and guidelines, equipment, and essential medicines). Descriptive statistics and logistic regression models were employed to present the study findings and analyze factors influencing facility readiness, respectively. Results Out of 403 health facilities providing NTD care nationally, 179, 183, and 197 also offer TB, HIV/AIDS, and malaria services, respectively. The majority of TB (90.1%), HIV/AIDS (89.6%), and malaria (90.9%) facilities offer soil-transmitted helminth services, followed by trachoma (range 87-90%). The percentages of the aforementioned facilities with at least one trained staff member for any type of NTD were 87.2%, 88.4%, and 82.1%, respectively. The percentage of facilities with guidelines for any type of NTD was relatively low (range 3.7-4.1%). Mebendazole was the most widely available essential medicine, ranging from 69 to 70%. The overall readiness analysis indicated that none of the included facilities (TB = 11.9%; HIV/AIDS = 11.6%; and malaria = 10.6%) were ready to offer NTD care. Specifically, a higher level of readiness was observed only in the domain of medicines across these facilities. Hospitals had better readiness to offer NTD care than did health centers and clinics. Furthermore, a significant associations were observed between facility readiness and factors such as facility type, region, presence of routine management meetings, types of NTD services provided, and fixed costs for services. Conclusions Ethiopian health facilities treating TB, HIV/AIDS, and malaria had an unsatisfactory overall service availability and a lack of readiness to provide NTD care. Given the existing epidemiological risks and high burden of TB, HIV/AIDS, malaria, and NTDs in Ethiopia, there is an urgent need to consider preparing and implementing a collaborative infectious disease care plan to integrate NTD services in these facilities.